The tissue effect of argon‐plasma coagulation with prior submucosal injection (Hybrid‐APC) versus standard APC: A randomized ex‐vivo study. Issue 5 (1st October 2014) - Manner, Hendrik; Neugebauer, Alexander; Scharpf, Marcus; Braun, Kirsten; May, Andrea; Ell, Christian; Fend, Falko; Enderle, Markus D
Abstract : Background: Thermal ablation for Barrett's oesophagus has widely been established in gastrointestinal endoscopy during the last decade. The mainly used methods of radiofrequency ablation (RFA) and argon‐plasma coagulation (APC) carry a relevant risk of stricture formation of up to 5–15%. Newer ablation techniques that are able to overcome this disadvantage would therefore be desirable. The aim of the present study was to compare the depth of tissue injury of the new method of Hybrid‐APC versus standard APC within a randomized study in a porcine oesophagus model. Methods: Using a total of eight explanted pig oesophagi, 48 oesophageal areas were ablated either by standard or Hybrid‐APC (APC with prior submucosal fluid injection) using power settings of 50 and 70 W. The depth of tissue injury to the oesophageal wall was analysed macroscopically and histopathologically. Results: Using 50 W, mean coagulation depth was 937 ± 469 µm during standard APC, and 477 ± 271 µm during Hybrid‐APC ( p  = 0.064). Using 70 W, coagulation depth was 1096 ± 320 µm (standard APC) and 468 ± 136 µm (Hybrid‐APC; p  = 0.003). During all settings, damage to the muscularis mucosae was observed. Using standard APC, damage to the submucosal layer was observed in 4/6 (50 W) and 6/6 cases (70 W). During Hybrid‐APC, coagulation of the submucosal layer occurred in 2/6 (50 W) and 1/6 cases (70 W). The proper muscle layer was only damaged during conventional APC (50 W: 1/6; 70 W: 3/6). Limitations: Ex‐vivo animal study with limited number of cases. Conclusions: Hybrid‐APC reduces coagulation depth by half in comparison with standard APC, with no thermal injury to the proper muscle layer. It may therefore lead to a lower rate of stricture formation during clinical application.